PENGGUNAAN MEDIA MANIPULATIF UNTUK MENINGKATKAN KEMAMPUAN MENGENAL KONSEP BILANGAN PADA ANAK USIA DINI (Studi Kasus di POS PAUD MELATI Kecamatan Regol Kota Bandung) - Nenden Susilowati (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2014)
This research is motivated by problems found in Pos Paud Melati Kecamatan Regol Kota Bandung, is the ability to recognize the concept of number of children in Pos Paud Melati is mean . It can be seen from the child 's response when asked about dealing with numbers . Therefore, research is conducted aiming to determine the increase in the ability to know the concept of numbers in early childhood with the use of manipulative media. The focus of his research are: 1 ) what media is used by teachers in improving the ability to know the number concept in children ? 2) How the application of manipulative media in children? 3) How the progress of the ability to recognize the concept of numbers in children after using manipulative media? The approach used in this study is a qualitative approach with descriptive analytical method. The collected data is the data observation, interview and documentation. The use of manipulative media is the application of the use of multiple media to improve the ability to recognize the concept of numbers that are given to children in Pos Paud Melati Kecamatan Regol Kota Bandung.The results showed that the use of manipulative media can increase the ability to know the concept of numbers in early childhood. Children can count many objects from 1-10 , counting by pointing objects ( familiar concept of numbers with objects ) to 10 , pointing to the symbol of numbers 1-10 , connect / pair emblem numbers with pictures of objects up to 10 ( no children were told to write ) better.The use of manipulative media has the advantage in the learning process, the child has learned and enthusiastic spirit better, as indicated by the response of the child when the teacher asks, actively involved in each activity and active cooperation with friends. The interaction between the child and her or teachers becomes more intertwined. This suggests that children learn in a fun atmosphere, so that the children can get to know and understand the concept of numbers either. That a barrier is the lack of creativity of teachers in creating and providing an attractive medium for children's learning.Efforts to overcome the above problems, it is recommended to increase the creativity of teachers internally in various ways to mastery (mastery) media , engage teachers in a variety of training and provide opportunities for teachers to continue to a higher level .